Clinical and follow-up study of bronchiolitis obliterans in pediatric patients in China. (December 2017) - Huang, Li; Xie, Yaping; Fan, Huifeng; Lu, Gen; Yu, Jialu; Chen, Chen; Yang, Diyuan
Bronchiolitis obliterans (BO) is in general a rare and life-threatening form of non-reversible obstructive lung disease in which the bronchioles are compressed and narrowed by fibrosis and/or inflammation. The purpose of this study was to evaluate the clinical features of BO in pediatric patients and explore its risk factors. The medical records of 35 pediatric patients with BO at Guangzhou Women and Children's Medical Center were evaluated. The age at onset of symptoms was 2–42 months (mean 13.3 ± 8.9 months), with age at diagnosis of 5 months–4 years (mean 17.8 ± 9.0 months). High-resolution computed tomography findings included mosaic pattern (100%), atelectasis (37.1%), air trapping (31.4%), and bronchiectasis (20.0%). Three patients received lung biopsies and mainly exhibited an inflammatory process surrounding the lumen of bronchioles. BO predominantly resulted from post-infectious causes (91.4%) which were primarily caused by adenovirus (50%), followed by Mycoplasma pneumoniae (46.7%) and influenza (20%). Pulmonary function tests (PFTs) showed severe and fixed airflow obstruction, decreased compliance, and increased resistance. No significant difference was found between before and after steroid treatment ( P > 0.05). Two patients died owing to severe pulmonary complications, one of whom had inherent immunodeficiency. Our study suggests that the occurrence of BO, especially post-infectious BO, in China is relatively high and might result from primary immunodeficiency diseases in severe cases. Recurrent aspiration pneumonia caused by congenital dysplasia of the larynx and vaccination not on schedule might be potential risk factors for persistent and recurrent BO.